Kidney Transplantation in a Patient Lacking Cytosolic Phospholipase A2 Proves Renal Origins of Urinary PGI-M and TX-M. Issue 4 (16th February 2018) - Mitchell, Jane A.; Knowles, Rebecca B.; Kirkby, Nicholas S.; Reed, Daniel M.; Edin, Matthew L.; White, William E.; Chan, Melissa V.; Longhurst, Hilary; Yaqoob, Magdi M.; Milne, Ginger L.; Zeldin, Darryl C.; Warner, Timothy D.
Abstract : Rationale: : The balance between vascular prostacyclin, which is antithrombotic, and platelet thromboxane A2, which is prothrombotic, is fundamental to cardiovascular health. Prostacyclin and thromboxane A2 are formed after the concerted actions of cPLA2 α (cytosolic phospholipase A2 ) and COX (cyclooxygenase). Urinary 2, 3-dinor-6-keto-PGF1α (PGI-M) and 11-dehydro-TXB2 (TX-M) have been taken as biomarkers of prostacyclin and thromboxane A2 formation within the circulation and used to explain COX biology and patient phenotypes, despite concerns that urinary PGI-M and TX-M originate in the kidney. Objective: : We report data from a remarkable patient carrying an extremely rare genetic mutation in cPLA2 α, causing almost complete loss of prostacyclin and thromboxane A2, who was transplanted with a normal kidney resulting in an experimental scenario of whole-body cPLA2 α knockout, kidney-specific knockin. By studying this patient, we can determine definitively the contribution of the kidney to the productions of PGI-M and TX-M and test their validity as markers of prostacyclin and thromboxane A2 in the circulation. Methods and Results: : Metabolites were measured using liquid chromatography-tandem mass spectrometry. Endothelial cells were grown from blood progenitors. Before kidney transplantation, the patient's endothelial cells and platelets released negligible levels of prostacyclin (measured as 6-keto-prostaglandin F1α ) and thromboxane A2 (measured as TXB2 ), respectively. Likewise, the urinary levels of PGI-M and TX-M were very low. After transplantation and the establishment of normal renal function, the levels of PGI-M and TX-M in the patient's urine rose to within normal ranges, whereas endothelial production of prostacyclin and platelet production of thromboxane A2 remained negligible. Conclusions: : These data show that PGI-M and TX-M can be derived exclusively from the kidney without contribution from prostacyclin made by endothelial cells or thromboxane A2 by platelets in the general circulation. Previous work relying on urinary metabolites of prostacyclin and thromboxane A2 as markers of whole-body endothelial and platelet function now requires reevaluation.